Co-digestion of tanning residues and sludge - Di Berardino, Santino (2010)
Codigestion experiments on sludge from tanneries’ industrial wastewater treatment plant (WWTP) mixed with chromium free (“green”) tanneries solid wastes were carried-out in a 15 m3 pilot plant reactor, operating at 20 days hydraulic retention time (HRT) and at mesophilic temperature (35 ºC). The goal was to evaluate the feasibility of a full-scale unit. Addition of “green” solid wastes improved biodegradability of the sludge and biogas production. The removal efficiencies of organic matter varied, according to the feedstock mixture. Averaged results are: COD and VS more than 55 %; TOC = 69 %. Hydrolysis of suspended volatile solids was initially moderate (36 %), but increased up to about 50 %, when the feedstock contained proteolytic enzymes. Fat removal was quite high (77 %). Biogas production was highly dependent from the fleshing content in the feedstock. Addition of 30 % by weight of fleshing to the sludge increased 4 times the average biogas production (from 3,85 m3/day to 14,62 m3/day). The maximum Biogas production rate was 38 liter/kg of feedstock. Fleshing biogas yield was found to be 630 l/kg Volatile Solids loaded, higher than the value recorded for the sludge (288 l/kg Volatile Solids loaded). Methane content in biogas was about 75 % CH4. The average biogas productivity of the reactor was 1.49 l/l/day. Sulphate removal carried-out by the biologic community (SO4 = ≥ 35%) increased Hydrogen sulphide concentration in the biogas up to 1800 ppm (average), a value higher than the limits allowed for use in internal combustion engines. Grinding and maceration of fleshing was hard, due to smell, repugnant look and high strength of its components. This feedstock must be pre-treated in order to avoid excess hydrogen sulphide and lime. Codigestion of “green” tannery wastes with sludge and others residues revealed technically feasible and a low cost solution for the environmental problem of these residues from small/average tanning factories. The potential biogas production for full scale plant is about 11 000 m3/day, making this solution refundable within 5 years. Codigestion allows substantial reduction in bio solids volume, pathogens, and odor, increasing landfill life. This is an important evolution on current solution and gives time to plan and implement new sustainable projects.